Malignant phyllodes tumor of the breast with predominant osteosarcoma and chondrosarcomatous differentiation: a rare case report and review of literature - Li, Wenfang; Ou, Qin; Li, Yingdong; Yuan, Linlin Yuan (Frontiers in Oncology, 2024)
Background Phyllodes tumors (PTs), which account for less than 1% of mammary gland tumors, composed of both epithelial and stromal components. If a malignant heterologous component is encountered, PT is considered malignant. Malignant phyllodes tumors (MPTs) only account for 8% to 20% of PTs. We report a case of MPT with osteosarcoma and chondrosarcoma differentiation and review the literature to discuss the differential diagnosis and therapy. Case presentation A 59-year-old Chinese woman come to our hospital because of a palpable mass she had had for 1 months in the left breast. Preoperative core needle biopsy (CNB) was performed on the left breast mass on January 11, 2023. Pathological diagnosis was malignant tumor, the specific type was not clear. Mastectomy and sentinel lymph node biopsy of the left breast was performed. No metastasis was found in 3 sentinel lymph nodes identified by carbon nanoparticles and methylene blue double staining. Heterologous osteosarcoma and chondrosarcomatous differentiation of phyllodes tumor were observed. Immunohistochemistry: spindle tumor cells ER(-), PR(-), HER-2(-), CK-pan(-), CK7(-), CK8(-), SOX10(-), S100(-), and MDM2(-), CK5/6(-), P63(-), P40(-) were all negative. CD34:(+), SATB2(+), P53(90% strong), CD68 (+), Ki-67(LI: about 60%). No ductal carcinoma in situ was found in the breast. Fluorescence in situ hybridization (FISH) indicated USP6 was negatively expressed on formalin-fixed, paraffin-embedded (FFPE) tissue sections. Conclusion MPTs are rare, and heterologous differentiation in MPTs is exceedingly rare. It could be diagnosed by pathology when metaplastic carcinoma, primary osteosarcoma, or myositis ossificans were excluded. This case could help clinicians to improve the prognosis and treatment of this disease.